Find the best solutions to your problems with the help of IDNLearn.com's expert users. Discover comprehensive answers to your questions from our community of knowledgeable experts.

Can someone solve this question ~
[tex] - 6 \: log_{3}(x - 2) = - 24[/tex]
[tex]ɴᵉᵉᵈ \: ɢᵉⁿᵘⁱⁿᵉ \: ᴀⁿˢʷᵉʳ[/tex]


Sagot :

[tex]\huge \sf༆ Answer ༄[/tex]

The value of x is ~

  • [tex] \sf \: 83[/tex]

[tex] \large \boxed{ \mathfrak{Step\:\: By\:\:Step\:\:Explanation}}[/tex]

Let's solve ~

  • [tex] \sf \: - 6 log_{3}(x - 2) = - 24[/tex]

  • [tex] \sf \: log_{3}(x - 2) = \dfrac{ - 24}{ - 6} [/tex]

  • [tex] \sf \: log_{3}(x - 2) = 4[/tex]

  • [tex]x - 2 = {(3)}^{4} [/tex]

  • [tex]x - 2= 81[/tex]

  • [tex]x = 81 + 2[/tex]

  • [tex]x = 83[/tex]

You're welcome spammy ~

The value of x from the given expression is 5

Laws of logarithm

Given the logarithm expression

  • [tex]-6log_3(x-2)=-24[/tex]

According to the law of logarithm, if [tex]log_ab=c, \ hence \ b= a^c[/tex]

Applying this law to the given question, we can see that:

[tex](x-2)^{-6}=3^{-24}\\(x-2)^6=3^{24}\\(x-2)^6=3^6\\[/tex]

Cancel out the exponents to have:

x - 2  = 3

x = 2 + 3

x = 5

Hence the value of x is 5

Learn more on logarithm here; https://brainly.com/question/25710806